P110 Fluticasone propionate/formoterol fumarate combination therapy is more efficacious in improving lung function than its individual components in patients with asthma. (2nd December 2011) - Price, D; Papi, A; Kaiser, K; Grothe, B; Lomax, M; McIver, T
Abstract : Introduction and Objectives: Combination therapy with an inhaled corticosteroid (ICS) and a long-acting ß2 -agonist (LABA) is the most effective treatment option for patients with asthma uncontrolled with ICS monotherapy.1 In practice, asthma symptoms remain uncontrolled or only partly controlled in many patients. A new therapy option for asthma combining the ICS fluticasone propionate (FLUT) and the LABA formoterol fumarate (FORM) in a single aerosol inhaler (FLUT/FORM; flutiform ® ), has been developed at doses of 100/10, 250/10 and 500/20 μg for twice-daily administration. In this analysis, data were pooled from up to five randomised, double-blind, parallel-group studies in order to assess the efficacy of FLUT/FORM in terms of improvement in lung function (as indicated by change in FEV1 ). Methods: The analysis included adults and adolescents with a range of asthma severities who were treated for 8 or 12 weeks with FLUT/FORM (100/10, 250/10 or 500/20 μg twice daily) or the equivalent nominal dose of FLUT monotherapy (100, 250 or 500 μg twice daily; five studies) or FORM monotherapy (10 μg twice daily; three studies). Results: FLUT/FORM was associated with a significantly greater improvement in lung function, as indicated by change in FEV1, compared with its individual components (Abstract P110 table 1 ). FLUT/FORM was superior to FORM with regard to change in pre-dose FEV1 from baseline to study end; the least-squares (LS) mean difference for FLUT/FORM vs FORM was 0.13 l (95% CI 0.07 to 0.19; p<0.001). Similarly, FLUT/FORM was superior to FLUT with regard to change in FEV1 from pre-dose at baseline to 2 h post-dose at study end (LS mean difference FLUT/FORM vs FLUT 0.15 L [95% CI 0.10 to 0.19; p<0.001]). Conclusions: The combination of fluticasone/formoterol in a single aerosol inhaler is more effective than fluticasone or formoterol given alone in improving lung function for patients with a range of asthma severities.